2020
DOI: 10.1016/j.arth.2020.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Why Reintervention After Total Knee Arthroplasty Fails? A Consecutive Cohort of 1170 Surgeries

Abstract: Background: The aim of this study was to analyze why contemporary reintervention after total knee arthroplasty (RiTKA) fails. Methods: Between January 2006 and December 2010, from a multicenter cohort of 1170 RiTKAs, we assessed all failures of RiTKA requiring additional surgery. All indications for the index reintervention were included. The minimum follow-up period was 3 years. Results: A total of 192 (16.4%) patients required additional surgery after RiTKA (re-reintervention). The mean follow-up period was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Bozic and coworkers analyzed reasons for rTKA in the US between 2005 and 2010 and reported PJI as reason for surgical revision to be 25% 12 . Other studies assessing reasons for reinterventions after primary TKA reported infection to be reason for rTKA in 30.3% 15 and 20.3% of the cases, respectively 16 . An analysis from two orthopedic centers in Germany reported PJI accounting for rTKA from 14.5% through 26.8%, depending on time after index total knee arthroplasty 17 , which corresponds with reported higher incidence rates of rTKA due to PJI compared to aseptic loosening early after index TKA 10,18 .…”
Section: Discussionmentioning
confidence: 93%
“…Bozic and coworkers analyzed reasons for rTKA in the US between 2005 and 2010 and reported PJI as reason for surgical revision to be 25% 12 . Other studies assessing reasons for reinterventions after primary TKA reported infection to be reason for rTKA in 30.3% 15 and 20.3% of the cases, respectively 16 . An analysis from two orthopedic centers in Germany reported PJI accounting for rTKA from 14.5% through 26.8%, depending on time after index total knee arthroplasty 17 , which corresponds with reported higher incidence rates of rTKA due to PJI compared to aseptic loosening early after index TKA 10,18 .…”
Section: Discussionmentioning
confidence: 93%
“…With aseptic loosening, infection is a major cause for arthroplasty revision, especially in early failures after TKA (2). In a recent French study on a cohort of 1,170 reinterventions after TKA, prosthetic joint infection (PJI) accounts for almost 50% of total revision (3). PJIs occur after 1-7% of TJA (4).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to resolving stiffness and MFI, our report suggests that revision into KA resolves these complications, at least in part. rTKA performed for stiffness using traditional techniques is complicated by recurrence of stiffness with reported rates between 7.1% and 49% [1,[24][25][26][27][28]. In all these prior studies, however, revision TKA was performed according to MA principles.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the etiologies for revision total knee arthroplasty (rTKA) are infection, aseptic loosening, instability and stiffness [1]. In particular, rTKA for stiffness or instability is a complex procedure and often results in unreliable clinical outcomes with a high rate of complications including recurrence of stiffness and inferior survival rates compared to primary TKA [2,3].…”
Section: Introductionmentioning
confidence: 99%